An Instructive Treatment of a Generalization of Găvruţă’s Stability Theorem - Gselmann, Ester; Száz, Árpád (Sarajevo Journal of Mathematics, 2024)
We prove several useful theorems on Hyers sequences and their pointwise limits in quite natural ways which make a straightforward generalization of Găvruţă''s stability theorem rather plausible. 2000 Mathematics Subject Classification. 20M15, 39B52, 39B82